Self‐directed self‐management interventions to prevent or address distress in young people with long‐term physical conditions: A rapid review - Nadia Corp; Lucy Bray; Carolyn A. Chew‐Graham; Kay Polidano; Tamsin Fisher; Adam D. Farmer; Megan McDermott‐Hughes; Benjamin Saunders (Wiley, 2023)
Abstract Background Comorbid distress in adolescents and young adults with physical long‐term conditions (LTCs) is common but can be difficult to identify and manage. Self‐directed self‐management interventions to reduce distress and improve wellbeing may be beneficial. It is unknown, however, which intervention characteristics are successful in supporting young people. This rapid review aimed to identify characteristics of self‐directed self‐management interventions that aimed, in whole or part, to address distress, wellbeing or self‐efficacy in this population. Methods A systematic search was conducted for relevant controlled studies in six databases. Data on study settings, population, intervention characteristics, outcome measures, process measures and summary effects were extracted. The risk of bias was assessed using the Cochrane Risk of Bias tool v1, and the strength of evidence was rated (informed by Grading of Recommendations, Assessment, Development and Evaluations). Patient and public involvement members supported the review process, including interpretation of results. The rapid review was registered with PROSPERO (ID: CRD42021285867). Results Fourteen studies were included, all of which were randomised trials. Heterogeneity was identified in the health conditions targeted; type of intervention; outcome measures; duration of intervention and follow‐up. Three had distress, wellbeing or self‐efficacy as their primary outcome. Four modes of delivery were identified across interventions-websites, smartphone applications, text messages and workbooks; and within these, 38 individual components. Six interventions had a significant benefit in mental health, wellbeing or self‐efficacy; however, intervention characteristics were similar for beneficial and non‐beneficial interventions. Conclusions There is a paucity of interventions directly targeting distress and wellbeing in young people with physical LTCs. In those identified, the heterogeneity of interventions and study design makes it difficult to identify which characteristics result in positive outcomes. We propose the need for high‐quality, evidence‐based self‐management interventions for this population; including (1) more detailed reporting of intervention design, content and delivery; (2) robust process evaluation; (3) a core outcome set for measuring mental health and wellbeing for self‐management interventions and (4) consistency in follow up periods. Public Contribution Seven young people with an LTC were involved throughout the rapid review, from the development of the review protocol where they informed the focus and aims, with a central role in the interpretation of findings.